(untitled) - Lilly, Sharon (Chelsea, Mich., 1999)
This the most useful information available to the golf course superintendent, course architect, and manager! It is written specifically for the golf industry, and gives you the tool you need to manage one of your course's most important assets--trees!
Keywords: Golf courses,Khóa học Golf; Management,Quản trị